2011
DOI: 10.1007/s00330-011-2138-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional ultrasound imaging in differently aggressive breast cancer xenografts using two novel ultrasound contrast agents (BR55 and BR38)

Abstract: BR38 and BR55 are well suited to characterising and distinguishing breast cancers with different angiogenesis and aggressiveness. Long-circulating BR38 MB allow extensive 3-dimensional examinations of larger or several organs. BR55 accumulation faithfully reflects the VEGFR2 status in tumours and depicts even small differences in angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 35 publications
4
67
0
Order By: Relevance
“…Whereas the transmembrane receptor tyrosine kinase VEGFR-2, which activates the PI3K/Akt/mTOR pathway and mediates endothelial cell proliferation, is mainly expressed on activated endothelium, the cell adhesion molecule α v ß 3 integrin, which binds to arginine-glycine-aspartic acid (RGD)-containing proteins and peptides, is up-regulated on tumor endothelium and on interstitial and tumor cells [7][8][9]. Importantly, as reported by previous studies [10][11][12], molecular ultrasound enables the non-invasive discrimination between breast neoplasms of different malignancy in mice and rats. In addition, phase II clinical trials have been recently launched evaluating the diagnostic potential of VEGFR-2-targeted microbubbles (BR55) using ultrasound in patients with breast or ovarian cancer (www.clinicaltrialsregister.eu, EudraCT: 2012-000699-40) and prostate cancer (www.clinicaltrials.gov, NCT02142608).…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Whereas the transmembrane receptor tyrosine kinase VEGFR-2, which activates the PI3K/Akt/mTOR pathway and mediates endothelial cell proliferation, is mainly expressed on activated endothelium, the cell adhesion molecule α v ß 3 integrin, which binds to arginine-glycine-aspartic acid (RGD)-containing proteins and peptides, is up-regulated on tumor endothelium and on interstitial and tumor cells [7][8][9]. Importantly, as reported by previous studies [10][11][12], molecular ultrasound enables the non-invasive discrimination between breast neoplasms of different malignancy in mice and rats. In addition, phase II clinical trials have been recently launched evaluating the diagnostic potential of VEGFR-2-targeted microbubbles (BR55) using ultrasound in patients with breast or ovarian cancer (www.clinicaltrialsregister.eu, EudraCT: 2012-000699-40) and prostate cancer (www.clinicaltrials.gov, NCT02142608).…”
Section: Introductionsupporting
confidence: 48%
“…S4+5). [5,6,[10][11][12][23][24][25]. However, besides a pilot phase study on breast cancer patients using radiolabeled α V ß 3 -targeted RGD peptides and PET demonstrating a significant probe uptake in the primary lesion and in the metastases [19], clinical studies comparing the diagnostic power of functional vs. molecular imaging for differentiating (mammographically) suspect tumors or for monitoring recurrent lesions upon breast cancer surgery have not yet been reported.…”
Section: Endothelial Vegfr-2 Levels But Not Vascular Area Fractionsmentioning
confidence: 99%
“…Therefore, microbubbles are highly suitable for molecular imaging of angiogenic and inflamed endothelial surfaces. 38 CEUS was used successfully in preclinical trials for tumor imaging [39][40][41] and thrombus characterization. 42 Moreover, anti-vascular cell adhesion molecule-1 antibody-coated microbubbles could localize successfully to atherosclerotic plaques in the aortic arch.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the assistance of ARF, recent studies have also demonstrated ultrasound targeted molecular imaging in large vessel environments using some new techniques [23], [50], [52]. In summary, state-of-the-art ultrasound molecular imaging methods have demonstrated efficacy in pre-clinical studies for detection and monitoring of various types of cancers [79], [155], [156] as well as cardiovascular inflammation [39], [138]. However, these approaches possess some limitations such as requiring a "control injection" (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical success of ultrasound molecular imaging has been demonstrated in small blood vessel environments for various diseases including breast [31], [34], [79], prostate [155], [165] and pancreatic [71] cancers, atherosclerosis [39], [40], [137], and inflammatory diseases of the bowels [94]. In these studies, various imaging strategies have been used to address the challenge of differentiating the signal arising uniquely from bound adherent microbubbles from the signals attributable freely circulating microbubbles and tissue.…”
Section: Introductionmentioning
confidence: 99%